EPCO-30. IDENTIFICATION OF PRECANCEROUS CELLS LEADING TO INTRATUMORAL HETEROGENEITY IN GLIOBLASTOMA. (14th November 2022) - Kim, Hyun Jung; Cha, Do Hyeon; Kim, Keon Woo; Kim, Myeong Heui; Park, Jung Won; Kim, Ja Hye; Yoon, Seon Jin; Kang, Seok-Gu; Lee, Jeong Ho
Abstract: Glioblastoma (GBM) is the most common and aggressive primary brain cancer in adults. Although multiple oncogenic mutations have been identified in neural stem cells of the subventricular zone (SVZ) in humans, the dynamic process of how tumor initiation begins with a mutation-harboring stem cells remains elusive. To better understand how GBM evolves, we analyzed longitudinal transcriptomic changes of mutation-harboring stem cells using a spontaneous, somatic GBM animal model with EGFRvIII, TP53, PTEN mutations. Using single-cell RNA sequencing, we have identified precancerous cell populations originating from oligodendrocyte precursor cells, with increased proliferation and decreased capacity to differentiate into oligodendrocytes. The precancerous cell populations undergo malignant transformation to become heterogeneous cancer cells characterized by immune evasion, mesenchymal transition, and cell cycle. We further identified the precancerous populations in the SVZ of human GBM patients with chromosomal aberrations. Our findings suggest that GBM evolution is closely related to oligodendrocyte precursor cell specification, and the time-dependent transcriptomic changes in precancerous cells is a novel therapeutic target for tumor evolution.